Long-circulating delivery of bioactive polysaccharide from radix ophiopogonis by PEGylation - Lin X (Dove Medical Press, 2011)
Xiao Lin1,2, Zhuo-Jun Wang2, Fang Huang3, Shuang Liang1, Lan Shen2, Yi Feng1, Ke-Feng Ruan11Engineering Research Center of Modern Preparation Technology of TCM of Ministry of Education, Shanghai University of Traditional Chinese Medicine, 2College of Chinese Materia Medica, Shanghai University of Traditional Chinese Medicine, 3Department of Nephrology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of ChinaBackground: Radix ophiopogonis polysaccharide (ROP) has been found to be effective against myocardial ischemia. One of main problems with its use is its short in-vivo half-life, which makes the development of an effective delivery system necessary. To achieve better therapeutic effects and patient compliance by prolonging its retention in plasma and increasing its distribution in targets, ROP was PEGylated (PEG, polyethylene glycol) in this study.Methods: Through a moderate coupling reaction between hydroxyl-activated ROP and amino-terminated methoxy-PEG (mPEG) (30 or 40 kDa), together with a greater than 1 molar ratio of ROP to mPEG in reaction, long-circulating and potentially bioactive PEGylated ROPs, with PEG grafting number of ~1.0, were prepared, characterized, and the pharmacokinetics evaluated.Results: Relative to ROP, whose half-life was approximately 0.7 hours, the two conjugates prepared, following intravenous administration, showed markedly prolonged retention in systemic circulation with half-lives in blood of 78.4 and 88.3 hours, respectively. When given subcutaneously, their in-vivo mean residence times were further markedly prolonged by the slow absorption phase. They were found to be well absorbed after subcutaneous administration, with absolute bioavailability being 75.4% and 43.9%, respectively.Conclusion: With apparent molecular masses not exceeding 43 kDa, the conjugates prepared have been and will be demonstrated to have prominent advantages for ROP delivery, such as: the good absorption following subcutaneous, intramuscular, or other ways of administration; the effective utilization of the enhanced permeability and retention effect caused by ischemia; and the rapid diffusion within target tissues.Keywords: radix ophiopogonis polysaccharide, polyethylene glycol, conjugation, pharmacokinetics